Morphologic, Immunohistochemical, and Molecular Distinction Between Fibroepithelioma of Pinkus and "Fenestrated" Basal Cell Carcinoma. (July 2020) - Russell-Goldman, Eleanor; Lindeman, Neal I.; Laga, Alvaro C.; Hanna, John
Abstract : Abstract: Fibroepithelioma of Pinkus (FEP) is a rare cutaneous neoplasm with a characteristic fenestrated architecture and a prominent spindle cell stromal component and which invariably pursues an indolent course. The classification of FEP has been much debated since its first description in 1953, with some arguing that it represents a variant of a basal cell carcinoma (BCC) while others view it as a variant of a trichoblastoma. Multiple previous immunohistochemical studies aiming to clarify this issue have yielded conflicting results. To date, there have been no molecular studies of FEP. We identified 16 cases of fenestrated follicular neoplasms and classified them as BCC or FEP based solely on histomorphologic criteria. CK20 immunohistochemistry supported this classification scheme, with FEP showing significantly more CK20-positive Merkel cells than BCC. We then analyzed a subset of these tumors by a targeted next-generation DNA sequencing platform. All the BCC cases harbored pathogenic PTCH1 mutations, confirming the diagnosis. By contrast, none of the FEP cases harbored a PTCH1 mutation or indeed any mutation known to be causally linked to the development of BCC. Our results suggest that FEP can be distinguished from BCC on morphologic, immunohistochemical, and molecular genetic grounds. We argue that FEP is better considered a benign follicular neoplasm and support its classification as a variant of trichoblastoma.